The Financial Literacy of Young People: Socioeconomic Status, Language Background, and the Rural-urban Chasm - Ali, Paul; Anderson, Malcolm; McRae, Cosima; Ramsey, Ian (Australian and International Journal of Rural Education, 2016)
In this paper we report the results of a survey of financial literacy levels among Australian secondary school students. While key issues concerning financial literacy among adolescents is fairly well known, and governments see the urgency of addressing low levels of such literacy among a vulnerable cohort, less is understood about the variation of knowledge levels among young people. In this paper we identify the gap between urban and rural survey participants in respect of their financial literacy, and attempt to locate the contrasting knowledge levels in a setting that includes socioeconomic status and language background.